1999
DOI: 10.1021/ie990149n
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Wet Air Oxidation:  Synergistic Rate Acceleration upon Effluent Recirculation

Abstract: Wet air oxidation (WAO) reactions of cellobiose, phenol, and syringic acid were carried out under mild conditions (155°C; 0.93 MPa O 2 ; soluble catalyst, Na 5 [PV 2 Mo 10 O 40 ]). Initial oxidation rates were rapid but decreased to small values as less reactive oxidation products accumulated. Recalcitrant oxidation products were consumed more rapidly, however, if additional cellobiose or phenol was added, a procedure equivalent to recirculation of WAO-reactor effluent. A halffraction, factorial investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
(27 reference statements)
2
11
1
Order By: Relevance
“…Shende and Levec (1999) found that the conversion of formic acid was about 11% higher when it was mixed with equal molar of acetic acid under the same operating conditions. Similar evidence was found by Birchmeier et al (2000), who added cellobiose or phenol to solutions containing recalcitrant products of incomplete oxidation and resulted in enhanced oxidation of the recalcitrant low molecular weight acids, and Mishra et al (1995) experienced a similar trend when oxidizing diethanolamine and morpholine. Recently, Vicente and Diaz (2003) found that the degradation rate of thiocyanate was significantly enhanced when simultaneously oxidized together with phenol.…”
Section: Introductionsupporting
confidence: 73%
“…Shende and Levec (1999) found that the conversion of formic acid was about 11% higher when it was mixed with equal molar of acetic acid under the same operating conditions. Similar evidence was found by Birchmeier et al (2000), who added cellobiose or phenol to solutions containing recalcitrant products of incomplete oxidation and resulted in enhanced oxidation of the recalcitrant low molecular weight acids, and Mishra et al (1995) experienced a similar trend when oxidizing diethanolamine and morpholine. Recently, Vicente and Diaz (2003) found that the degradation rate of thiocyanate was significantly enhanced when simultaneously oxidized together with phenol.…”
Section: Introductionsupporting
confidence: 73%
“…These results suggest an interaction between the two species during the oxidation process, cyanide being easily oxidizable and thiocyanate being more refractory to oxidation [29]. Synergism phenomena has been frequently reported by several authors during the wet oxidation of different compounds such as: mixtures of simple alcohols and acetic acid [30], low molecular mass carboxylic acids [31], phenol, cellobiose and low molecular weight acids [32], nitrobenzene and phenol [25], and dinitrophenol and trinitrophenol [33]. During a synergistic mechanism, one of the species (cyanide in this case) is a better radical generator than the less easily oxidizable species (thiocyanate).…”
Section: Resultsmentioning
confidence: 51%
“…Some studies gave the indirect evidences of free radical reactions. Co-oxidation is one of them, which involves the oxidation of an organic compound by free radical intermediates generated from another organic compound [180][181][182][183]. Another is to hinder or promote the free radical reactions using inhibitors such as t-butanol [184,185] or promoters like hydrogen peroxide and hydroquinone [184,186], respectively.…”
Section: Reaction Mechanisms and Pathwaysmentioning
confidence: 99%